Decellularized Wharton's jelly extracellular matrix as a promising scaffold for promoting hepatic differentiation of human induced pluripotent stem cells. Issue 4 (11th November 2018) - Kehtari, Mousa; Beiki, Bahareh; Zeynali, Bahman; Hosseini, Fatemeh Sadat; Soleimanifar, Fatemeh; Kaabi, Mohammad; Soleimani, Masoud; Enderami, Seyed Ehsan; Kabiri, Mahboubeh; Mahboudi, Hossein
Abstract: Liver tissue engineering as a therapeutic option for restoring of damaged liver function has a special focus on using native decellularized liver matrix, but there are limitations such as the shortage of liver donor. Therefore, an appropriate alternative scaffold is needed to circumvent the donor shortage. This study was designed to evaluate hepatic differentiation of human induced pluripotent stem cells (hiPSCs) in decellularized Wharton's jelly (WJ) matrix as an alternative for native liver matrix. WJ matrices were treated with a series of detergents for decellularization. Then hiPSCs were seeded into decellularized WJ scaffold (DWJS) for hepatic differentiation by a defined induction protocol. The DNA quantitative assay and histological evaluation showed that cellular and nuclear materials were efficiently removed and the composition of extracellular matrix was maintained. In DWJS, hiPSCs‐derived hepatocyte‐like cells (hiPSCs‐Heps) efficiently entered into the differentiation phase (G1) and gradually took a polygonal shape, a typical shape of hepatocytes. The expression of hepatic‐associated genes ( albumin, TAT, Cytokeratin19, and Cyp7A1 ), albumin and urea secretion in hiPSCs‐Heps cultured into DWJS was significantly higher than those cultured in the culture plates (2D). Altogether, our results suggest that DWJS could provide a proper microenvironment that efficiently promotes hepatic differentiation of hiPSCs. Abstract : Decellularized Wharton's jelly extracellular matrix could provide a proper microenvironment that efficiently promotes hepatic differentiation of human induced pluripotent stem cells.